2005
DOI: 10.1097/01.shk.0000180617.21564.b3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Myocardial Defects Under Extreme Acute Normovolemic Hemodilution With Hydroxyethyl Starch and Lactated Ringer's Solution

Abstract: Acute normovolemic hemodilution (ANH) has been proposed to avoid the risks of allogenic transfusion. In reference to its cellular effects, ANH reports in the literature are scarce. Using electron microscopy (EM), we evaluated the effects of ANH on cardiac function and myocardial structure. Twenty-five dogs were prospectively randomized to a control group (n = 5) or to undergo ANH with 6% hydroxyethyl starch (HES; n = 10) or lactated Ringer's solution (LR; n = 10) administered, respectively, at a ratio of 1:1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
13
0
3
Order By: Relevance
“…Alternative methods of conservation include meticulous hemostasis in surgical patients, 129 erythropoietin administration, 130,131 use of factor VIIa 132 or desmopressin, 133 use of hemodilution, 134 reduction of phlebotomy losses, and reduction of trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods of conservation include meticulous hemostasis in surgical patients, 129 erythropoietin administration, 130,131 use of factor VIIa 132 or desmopressin, 133 use of hemodilution, 134 reduction of phlebotomy losses, and reduction of trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies, performed with different species and various situations, demonstrated critical hematocrit levels between 10 and 15% (Fraga et al, 2005;Hiebl et al, 2010;van Bommel et al, 2002). In a study performed with dogs submitted to continuous hemodilution with lactated Ringer´s solution, a decrease in heart function (ejection fraction and fractional shortening) was observed when hemoglobin levels reached 3.5 g/dL.…”
Section: Heart Tolerance To Acute Anemiamentioning
confidence: 99%
“…In a study performed with dogs submitted to continuous hemodilution with lactated Ringer´s solution, a decrease in heart function (ejection fraction and fractional shortening) was observed when hemoglobin levels reached 3.5 g/dL. Also, at this hemoglobin level, oxygen delivery decreased to the point of impairing oxygen consumption (Fraga et al, 2005).…”
Section: Heart Tolerance To Acute Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Tem sido sugerido que o HES 130/0,4 pode reduzir a resposta inflamatória em pacientes submetidos a cirurgias abdominais de grande porte quando comparado à solução cristalóide (Ringer lactato) (Lang et al, 2003 (Karanko et al, 1987;Boldt, 2000) No nosso meio, a utilização do HES é bastante estudada, do ponto de vista experimental, em técnicas de hemodiluição normovolêmica aguda quanto aos seus efeitos no coração (Fraga et al, 2005), nos pulmões e nos diferentes órgãos . Esses estudos demonstraram que os amidos são superiores aos cristaloides em preservar, durante a hemodiluição, a estrutura celular e orgânica dos órgãos estudados.…”
Section: Hidroxietilamido (Hes)unclassified